2019
DOI: 10.3390/microorganisms7110554
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Distribution, and Phylogeny of Type Two Toxin-Antitoxin Genes Possessed by Cronobacter Species where C. sakazakii Homologs Follow Sequence Type Lineages

Abstract: Cronobacter species are a group of foodborne pathogenic bacteria that cause both intestinal and systemic human disease in individuals of all age groups. Little is known about the mechanisms that Cronobacter employ to survive and persist in foods and other environments. Toxin–antitoxin (TA) genes are thought to play a role in bacterial stress physiology, as well as in the stabilization of horizontally-acquired re-combinatorial elements such as plasmids, phage, and transposons. TA systems have been implicated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…As is the case for many enteric pathogens, another common feature possessed among Cronobacter species is that they carry plasmids, which are known to be involved in contributing to genomic plasticity, bacterial virulence, and survival [40]. In general, such plasmids have been found among members of the Enterobacteriaceae that encode a diversity of virulence factors, such as harboring genes for antibiotic resistance, toxins, adherence factors, and secretion systems (types 3, 4, and 6), and it is thought that plasmid-borne virulence genes (or gene clusters) are acquired through horizontal gene transfer (HGT) [40][41][42][43][44][45][46]. In silico analysis of such plasmids harbored by Cronobacter species suggests that this common theme holds true here as well [47].…”
Section: Common Themes In Cronobacter Virulencementioning
confidence: 99%
See 2 more Smart Citations
“…As is the case for many enteric pathogens, another common feature possessed among Cronobacter species is that they carry plasmids, which are known to be involved in contributing to genomic plasticity, bacterial virulence, and survival [40]. In general, such plasmids have been found among members of the Enterobacteriaceae that encode a diversity of virulence factors, such as harboring genes for antibiotic resistance, toxins, adherence factors, and secretion systems (types 3, 4, and 6), and it is thought that plasmid-borne virulence genes (or gene clusters) are acquired through horizontal gene transfer (HGT) [40][41][42][43][44][45][46]. In silico analysis of such plasmids harbored by Cronobacter species suggests that this common theme holds true here as well [47].…”
Section: Common Themes In Cronobacter Virulencementioning
confidence: 99%
“…pESA3-like plasmids (synonymous with plasmids pCTU1, pCS2, pCSK29544_1, and pSP291-1) are thought to be examples of a prototypic virulence plasmid that was originally described by Franco et al [47]. Plasmid pEAS2 is similar to pCTU2, which are conjugative plasmids, and pCTU3 is a plasmid that contains gene clusters involved in heavy metal (Ag, Cu, and Arsenic) efflux (efflux pumps such as RND EPs); and maintenance of these plasmids seem to be under tight control by multiple toxin-antitoxin genes of both type I and type II classes of toxin-antitoxin (TA) genes [46,52,53,102,145]. TA genes are thought to help stabilize plasmids and mobile genetic elements or genetic cassettes, and they participate in the response to stressful growth conditions.…”
Section: Role Of Plasmidsmentioning
confidence: 99%
See 1 more Smart Citation
“…They are also involved in a persistence phenotype in some species, such as E. coli and Salmonella (Deter et al, 2017;Walling and Butler, 2019). Finkelstein et al (2019) found, in preliminary studies of C. sakazakii isolates, that two typical TA genes, fic and hipA, followed species-specific evolutionary lines. When expanding their focus to evaluate the presence of five TA in C. sakazakii, they found that some strains contained either a toxin or an antitoxin component but not both.…”
Section: Resultsmentioning
confidence: 99%
“…The TA genes play a fundamental role in the physiology of bacterial stress response, such as in stabilizing horizontally acquired mobile genetic elements and participating in a persistence phenotype in some species, including E. coli and Salmonella ( Deter et al, 2017 ; Walling and Butler, 2019 ). Finkelstein et al (2019) noted in preliminary studies with C. sakazakii isolates that 2 typical toxin genes, fic and hipA , followed the evolutionary lines of the species and that C. sakazakii ST1 strains were the only strains containing the 22 TA homologs.…”
Section: Discussionmentioning
confidence: 99%